Role Modelling Social Media Influencers on TikTok and Instagram in Enhancing Students’ Speaking in Digital Storytelling - Alfiandy Kamal; Dahniar (Didaktika: Jurnal Kependidikan, 2025)
This study aims to investigate the improvement of students' speaking skills by imitating social media influencers (SMI) on TikTok and Instagram through digital storytelling. In addition, this study also aims to find out how the students perceive the imitating technique and how the students create digital storytelling videos. There were 20 students participating in this study selected by purposive and convenience sampling. To accommodate the study's objectives, action research was applied, and a questionnaire adapted from the Technology Acceptance Model (TAM) was administered. This study reveals that students experienced a significant improvement in speaking by imitating SMI, proven by t-test data showing 0.000 < 0.05. The study also shows a rise in mean scores from the poor category to the fair category. Additionally, this study illustrates positive perceptions toward this technique, where students find this technique easy to implement and benefit from boosting their speaking skills. Furthermore, this study shows that students demonstrated several activities in creating digital storytelling, such as preparing tools, recording videos, editing footage, and publishing videos.